Wzorce zachowań integracyjnych państw członkowskich RWPG - Najlepszy, Eugeniusz (Wydział Prawa i Administracji UAM, 1990)
The subject-matter of the article is the model of strategic behaviour of socialist economy within the CMEA. It has been assumed that the purpose of strategic activity of each of the member-states is the attainment of optimum position of its national economy in the international division of labour within the CMEA. The choice of integration strategy is conditioned by many external (international division of labour and institutional integration structures) and internal factors. In the CMEA, a prevailing tendency with respect to integration is the extrapolation of hitherto existing trends, leading to a very limited perception of integration. Besides,, usually a very narrow group of state authorities understands, strategic prognoses and interprets correctly the situation. The outcome of activity presented in the model are three alternative types of reaction of economy in the integrational surrounding: defensive, adaptational and creative. In the historical perspective, the economies of the CMEA countries have not revealed any significant interest in any other response to integrational processes than the defensive reaction.
Integration strategy of socialist countries within the CMEA